Income, wealth and equal opportunities in Sweden - Pareliussen, Jon (OECD Publishing, 2017)
Sweden is an egalitarian society in international comparison, and has managed to combine equity with economic efficiency. Rapidly rising inequality and relative poverty from a historical low in the 1980s partly stem from ageing, changing family structures and migration. Living standards increased for all groups, but social benefits rose less than earned income. Incomes of newly-arrived immigrants and single mothers trailed the median. Bottlenecks in the migrant settlement process are costly to migrants and society, and high entry wages further slow integration. Spatial segregation leads to school segregation and potentially reduced social mobility for the least endowed, and rental regulations reduce the scope for settling where job opportunities are the best. Fast-growing capital incomes, likely linked to increasing wealth concentration and income shifting, increased inequality. Low intergenerational income mobility in the very top of the income distribution is a concern. Social benefits should be uprated more systematically and regressive housing-related taxation reformed to strengthen redistribution. Migrant settlement and integration need to be better coordinated and adapted to individual starting points. The number of wage subsidies and their administrative complexity should be reduced to ease labour market entry. Dysfunctional rental regulations should be reformed to increase mobility and limit spatial segregation. This working paper relates to the 2017 OECD Economic Survey of Sweden (www.oecd.org/eco/surveys/economic-survey-sweden.htm)
Keywords: Economics; Sweden